Nurse navigators and person‐centred care; delivered but not valued?. Issue 4 (1st March 2021) - Byrne, Amy‐Louise; Harvey, Clare; Baldwin, Adele
Abstract: Positioning the individual at the centre of care (person‐centred care [PCC]) is essential to improving outcomes for people living with multiple chronic conditions. However, research also suggests that this is structurally challenging because health systems continue to adopt long‐standing, episodic care encounters. One strategy to provide a more cohesive, individualised approach to care is the implementation of the nurse navigator role. Current research shows that although PCC is a focus of navigation, such care may be hindered by the rigid, systematised health services providing siloed specialist care. In this paper, we utilised a case study method to investigate the experiences of a nurse navigator and patient. The nurse navigator and the patient participated in individual interviews, the transcripts of which were analysed using critical discourse analysis. Findings from a larger research project suggest that traditional measures (hospital avoidance, emergency department usage) which work as the service objectives of the nurse navigator service have the potential to stifle the delivery of PCC. The analysis from this case study supports the broader findings and further highlights the need for improved alignment between service objectives and the health and well‐being of the individuals utilising the services.